Investigation of Japanese-specific alleles: Most are of Jomon lineage. Issue 1 (January 2015) - Yuasa, Isao; Umetsu, Kazuo; Adachi, Noboru; Matsusue, Aya; Nakayashiki, Nori; Fujihara, Junko; Akane, Atsushi; Harihara, Shinji; Jin, Feng; Ishikawa, Takaki
Highlights Three SNPs suggested the existence of Japanese-specific alleles on autosomes. Further study identified a total of 67 (nearly) Japanese-specific alleles. DNA samples from Jomon skeletons were also investigated. Most of those alleles were suggested to have originated from the Jomon lineage. These alleles would be useful as ancestry-informative markers.